Bloody nipple discharge in a 5-month-old male baby. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
Bloody nipple discharge was reported first time in newborns in 1983 (1). In some further surgically treated cases (2, 3) the bloody discharge proved to be due to a benign ectasia of the galactophore ducts associated with a modest inflammation and induced by hormonal stimuli. Exceptionally, bloody nipple discharge even in children (2) may be caused by a mammary carcinoma. From a clinical point of view, benign ectasia is usually bilateral and secretion is not spontaneous, but caused by nipple manipulation. Moreover, the problem regresses spontaneously in a period ranging from 2 weeks to 9 months (3). Ultrasonography unveils an inhomogeneous hypoechogenic area, which is expression of the duct ectasia and modest inflammation. In the exceptional cases of juvenile carcinoma the bloody discharge is unilateral, spontaneous and persistent. With the palpation a mass is appreciated.